Pengaruh Hipnoterapi Terhadap Tingkat Kecemasan Pada Pasien Kanker yang Menjalani Kemoterapi di Rumah Sakit Panti Nirmala Malang - Luluk Nur Aini; Cinthia Kartikaningtias (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Hypnotherapy is a proven and very effective method for treating mental illnesses including anxiety disorders. Cancer patients undergoing chemotherapy often experience effects such as anxiety. Cancer is a serious disease that impacts a patient's physical and emotional well-being. The aim of this study was to determine the effect of hypnotherapy on reducing anxiety levels in patients undergoing chemotherapy. The design in this research is a quasi experiment with one group pretest and posttest design. The sample consisted of 29 cancer patients undergoing chemotherapy at Panti Nirmala Hospital. The anxiety instrument used is the State-Trait Anxiety Inventory (STAI). The results of the study showed that most of the anxiety levels of patients undergoing chemotherapy at Panti Nirmala Hospital before receiving hypnotherapy were severely anxious, 22 (75.9%) and after hypnotherapy, the majority were mildly anxious, 17 (58.6%). Meanwhile, the Sig value. The Wilcoxon test is (0.000) <0.05 or /Z count/ > Z t table, namely (4.704>1.96) so it can be concluded that there is an effect of hypnotherapy on the anxiety of cancer patients undergoing chemotherapy at Panti Nirmala Hospital with different values ​​before and after hypnotherapy was -4.704. The conclusion is that there is an effect of hypnotherapy on the anxiety of cancer patients undergoing chemotherapy at Panti Nirmala Hospital. Hypnotherapy can be an alternative effort to increase the development of nursing knowledge in an effort to reduce anxiety in patients undergoing chemotherapy.